Relevansi Nilai-Nilai Pendidikan Islam dalam Buku Syair Gulung Ketapang Karya Mahmud Mursalin - Habibah, Alif Rohmah Nur; Mukarromah; Rizka Mahmulia (TAUJIH: Jurnal Pendidikan Islam, 2023)
This research aims to analyze the values of Islamic education contained in the book of Syair Gulung Ketapang by Mahmud Mursalin and to analyze the relevance of the values of Islamic education contained in the book of Syair Gulung Ketapang by Mahmud Mursalin with current developments. The approach used is a literature review approach. This type of research is qualitative research. Data collection techniques, namely note-taking techniques, document use techniques. The validity of the data in this research is triangulation techniques (source, investigator, and theory), as well as peer examination. The data analysis technique that the researcher carried out was structured into three steps, namely the data reduction stage, the data presentation stage, and the conclusion drawing or verification stage. The results of this research are (1) The values contained in the Ketapang rolled poetry were found to be the value of moral education, the value of monotheism education and the value of date education. (2) The relevance of the values of Islamic education contained in the book of Syair Gulung Ketapang is very relevant as a reference, considering the needs of modern society regarding the importance of carrying out correct actions in the Islamic view to face the changes of this increasingly modern era.